ChemInform Abstract: A Catalyst‐Free, One‐Pot, Three‐Component Approach for the Synthesis of 2‐[1‐Aryl‐2‐(azaaryl)ethyl]malononitriles via sp3 C—H Activation of 2‐Methyl Azaarenes. Issue 1 (17th December 2015) - Kumar, Nandigama Satish; Rao, L. Chandrasekhara; JagadeeshBabu, N.; Dileep Kumar, V.; Murthy, U. S. N.; Meshram, H. M.
Abstract: Some of the title compounds, e.g. (IV), (VI), and (IX) are identified as potent antibacterial agents.